2013
DOI: 10.1016/j.brainres.2013.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Altered hippocampal myelinated fiber integrity in a lithium-pilocarpine model of temporal lobe epilepsy: A histopathological and stereological investigation

Abstract: The damage of white matter, primarily myelinated fibers, in the central nervous system (CNS) of temporal lobe epilepsy (TLE) patients has been recently reported. However, limited data exist addressing the types of changes that occur to myelinated fibers inside the hippocampus as a result of TLE. The current study was designed to examine this issue in a lithium-pilocarpine rat model. Investigated by electroencephalography (EEG), Gallyas silver staining, immunohistochemistry, western blotting, transmission elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 53 publications
2
26
2
Order By: Relevance
“…The four rats that did not display SRS after 80 days were excluded. Similarly to previously reported findings (Goffin et al, 2007;Ye et al, 2013), SRS tended to occur in clusters with a duration of less than one min for each seizure. Fig.…”
Section: Epilepsy Induction and A Description Of The Animals Used In supporting
confidence: 77%
See 3 more Smart Citations
“…The four rats that did not display SRS after 80 days were excluded. Similarly to previously reported findings (Goffin et al, 2007;Ye et al, 2013), SRS tended to occur in clusters with a duration of less than one min for each seizure. Fig.…”
Section: Epilepsy Induction and A Description Of The Animals Used In supporting
confidence: 77%
“…The myelin sheath is critical for interneuronal communication, and the integrity of myelin is crucial for maintaining normal neuronal network function and sequential electrical impulse conduction. Although the myelin sheath has traditionally not been considered critical to the pathogenesis of epilepsy, recent reports have demonstrated that CNS myelin sheaths are affected in certain epilepsy patients (Concha et al, 2009;Nilsson et al, 2008;Scanlon et al, 2013;Schoene-Bake et al, 2009), and our previous study confirmed that demyelination of the hippocampus occurs in lithium-pilocarpine-induced epileptic rats (Ye et al, 2013). In addition, epileptic seizures have also been observed in patients with multiple sclerosis, a typical demyelinating disease of the CNS, and in different animal models with myelin diseases (Anderson and Rodriguez, 2011;Bloom et al, 2002;Eguibar and Cortes Mdel, 2010).…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…In agreement with other PTZ kindling [36,37], we have observed an increase in MDA levels and a decrease in the pool of antioxidant enzymes, as is evident from the decreased GSH content and activity of SOD and CATA in brain homogenates. This could be explained since an increased neuronal calcium ion concentration leads to mitochondrial dysfunction, cell damage, and epilepsy [38]. Additionally, reactive oxygen species generation can also support the induction of seizure activity by permitting an excessive increase in glutamate, inducing excitotoxicity [39].…”
Section: Discussionmentioning
confidence: 99%